Heated plant extracts as natural inhibitors of enzymatic browning: A case of the Maillard reaction - Vhangani, Lusani Norah; Van Wyk, Jessy (Journal of food biochemistry, 2021)
Enzymatic browning is the second largest cause of quality loss in fruits, vegetables, and seafood. Methods to prevent browning are the subject of great research interest in the field of Food Science and Technology. Numerous strategies for inhibiting enzymatic browning have been proposed in literature. Recent research is focused on finding alternative anti‐browning agents to synthetics such as sulfites. Amongst natural antioxidants, Maillard reaction products (MRPs) have proven to be effective. Although reviews have been published on the antioxidant and anti‐browning activity of MRPs, none of these focused solely on enzymatic browning inhibition mechanism of MRPs generated via heated plant extracts. Therefore, this review explores the common factors associated with the Maillard reaction (temperature, time, and concentration) and enzymatic browning inhibition (enzyme, substrate and reaction time) in order to confirm the activity and presence of MRPs in heated plant extracts. Practical applications Chemical food additives applied in prevention of enzymatic browning are subjected to scrutiny. Therefore, alternative natural compounds are sought after. Plant extracts have been applied, however, they tend to impart their characteristic natural flavor into the product. Heating of these plant extracts have been proven to reduce the “planty, herby” flavors, whilst producing Maillard reaction. Maillard reaction products are known to exhibit anti‐browning activity, and they are a cheap alternative to these chemical inhibitors. Therefore, these can be applied as potential anti‐browning agents in food products. Heated plant extracts inhibit enzymatic browning (EB). Maillard reaction products (MRPs) formed during heating of plant extracts are responsible for EB inhibition. Final stage MRPs exhibit better EB inhibition than intermediate and early stage products.